2018
DOI: 10.1111/tid.12930
|View full text |Cite
|
Sign up to set email alerts
|

Management of immunosuppressive therapy in liver transplant recipients who develop bloodstream infection

Abstract: Any reduction in the immunosuppressive therapy was common and was associated with worse outcome in LT recipients developing BSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Despite surgical developments in the field of transplantation, infectious complications remain a major cause of morbidity and mortality for pediatric patients after transplantation. Studies have showed that transplant patients who develop systemic infections could have a worse prognosis (25)(26)(27). In our study, it has been noted that infection rate reached 74.1%, and infection cases took up the majority of adverse events.…”
Section: Discussionsupporting
confidence: 49%
“…Despite surgical developments in the field of transplantation, infectious complications remain a major cause of morbidity and mortality for pediatric patients after transplantation. Studies have showed that transplant patients who develop systemic infections could have a worse prognosis (25)(26)(27). In our study, it has been noted that infection rate reached 74.1%, and infection cases took up the majority of adverse events.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, some experts believe that a reduction in immunosuppression may lead to higher mortality by increasing the capacity of the immune system to induce a systemic inflammatory response. 26 CMV is an immunomodulatory virus that cans favor bacterial infections. 27 Theoretically, CMV prevention could reduce this increased risk, 28 although recent consensus does not recommend CMV prophylaxis in the scenario of solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study including 157 liver transplanted patients documented immunosuppression reduction during bloodstream infection to be associated with worse outcomes. Specifically, reduction or discontinuation of at least one immunosuppressive drug was a significant risk factor for 28 days mortality …”
Section: Discussionmentioning
confidence: 99%